MANAJEMEN KURIKULUM DAN PEMBELAJARAN: STRATEGI PENINGKATAN KUALITAS PENDIDIKAN DI ERA DIGITAL - Emerentiana Rangkoly; Desti Rahayu (CV. ADIBA ASIHA AMIRA, 2025)
Curriculum and learning management are crucial aspects of the education system that influence the quality of education. This research aims to explore effective curriculum management strategies in the context of learning in the digital era. The methods used include literature review and qualitative analysis from various relevant sources. The findings indicate that the integration of technology in the curriculum, teacher training, and active student participation are key factors in enhancing the effectiveness of learning. This discussion provides recommendations for policymakers in designing a curriculum that is responsive to the changing times.